Conceptualization of the phenomenon of ecological values as a basic notion for professional training of future natural sciences teachers - Valentyn Rohoza (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2019)
The article conceptualizes the phenomenon of "ecological values", which is the basis of educational and professional training of future teachers of natural sciences. The research focuses on identifying the system of values and their hierarchy in order to achieve at least two key results: 1) the formation of a higher level of a value sphere of future natural sciences teachers and improvement of the process of acquired values transfer; 2) improvement of learning outcomes (improvement in behavior, awareness, knowledge). Based on the extensive analysis of the scientific literature, the research suggests the meaningful characteristic of the formulated ecological values of the future natural sciences teachers. As a result, the research has considered the ecological values of future natural sciences teachers as an integrated value block in the system of their value orientations.